To see or be seen? The grounds of a place-based university - Sturm, Sean; Turner, Stephen (Interstices: Journal of Architecture and Related Arts, 2021)
In “The Tyranny of Transparency,” Marilyn Strathern argues that, in the neoliberal university, “visibility as a conduit for knowledge is elided with visibility as an instrument for control.” It is, but we would go further. After Deleuze, we would describe the apparatus of the university as an “optical machine”: it is “made of lines of light … distributing the visible and the invisible.” The drive to transparency, or panoptics, dominates the university today – from audit to architecture – and serves what Levien de Cauter calls “transcendental capitalism.” But it obscures a shadow discourse, or scotoptics, which hides invisible “lines of flight” and “fracture” that are transversal to transparency and transcendental capitalism. What this shadow discourse discloses about our university is that it is a transcendental-colonial-Maori place, a place that is palimpsestic and contested, a whenua tautohetohe (contested territory). We need to know that our university is more than it seems to be able to conceive of it as a “pluriversity,” a place of possibilities, upbuilding and practical wisdom: a wānanga (place of learning).